(untitled) (Economic studies journal, 2018)
The aim of this study is to investigate the illegal immigration in Africa and analyze its causes and its results, as well its impacts upon the relations between the nations. the study also studies the impact of the illegal immigration upon the human , the community and the biases of the international law and the international relations. Furthermore, the study tries to clarify the efforts which have been done by the international community to face the illegal immigration within taking in account the human rights of the immigrant. In this study, the descriptive approach has been applied to analyze the illegal immigration and its causes. Moreover, the legal approach applied by emphasize the legal biases which address the illegal immigration internationally and regionally, and stress the significant internationally and regionally agreements. A number of results have been highlighted, firstly, there is an interplay responsibility between the receivable and origin countries towards the immigrants. Secondly, the main cause of the illegal immigration is the wars which taken place in the origin countries. Thirdly, the illegal immigration is seen as a big lost for the origin countries in terms of the human resource.